Sleep deprivation does not affect neuronal susceptibility to mild traumatic brain injury in the rat - Caron AM (Dove Medical Press, 2015)
Aimee M Caron, Richard Stephenson Department of Cell and Systems Biology, University of Toronto, Toronto, ON, Canada Abstract: Mild and moderate traumatic brain injuries (TBIs) (and concussion) occur frequently as a result of falls, automobile accidents, and sporting activities, and are a major cause of acute and chronic disability. Fatigue and excessive sleepiness are associated with increased risk of accidents, but it is unknown whether prior sleep debt also affects the pathophysiological outcome of concussive injury. Using the “dark neuron” (DN) as a marker of reversible neuronal damage, we tested the hypothesis that acute (48 hours) total sleep deprivation (TSD) and chronic sleep restriction (CSR; 10 days, 6-hour sleep/day) affect DN formation following mild TBI in the rat. TSD and CSR were administered using a walking wheel apparatus. Mild TBI was administered under anesthesia using a weight-drop impact model, and the acute neuronal response was observed without recovery. DNs were detected using standard bright-field microscopy with toluidine blue stain following appropriate tissue fixation. DN density was low under home cage and sleep deprivation control conditions (respective median DN densities, 0.14% and 0.22% of neurons), and this was unaffected by TSD alone (0.1%). Mild TBI caused significantly higher DN densities (0.76%), and this was unchanged by preexisting acute or chronic sleep debt (TSD, 0.23%; CSR, 0.7%). Thus, although sleep debt may be predicted to increase the incidence of concussive injury, the present data suggest that sleep debt does not exacerbate the resulting neuronal damage. Keywords: sleep deprivation, concussion, traumatic brain injury, dark neuron, neurodegeneration, rat cortex